Pengaruh Metode Resitasi Terhadap Hasil Belajar Siswa Mata Pelajaran Sejarah Kebudayaan Islam (SKI) Kelas VIII Di Madrasah Tsanawiyah Muhammadiyah 8 Sidokelar Paciran Lamongan - Chimlatul Bahriyah; Maftuhah (jurnal Mahasiswa Pencerah, 2022)
This study aims to: (1) Knowing the application of the Recitation method to SKI subjects (2) Knowing the effect of the Recital method on student learning outcomes in SKI class VIII subjects at MTs. Muhammadiyah 8 Sidokelar.The research method used is quantitative research. The sampling technique was carried out by the saturated sampling method. So that the sample used in this study was class VIII students at MTs. Muhammadiyah 8 Sidokelar, totaling 17 students. While the data analysis techniques used are using parametric tests: (1) Validity Test, (2) Reliability Test, (3) Normality Test, (4) Homogeneity, (5) Product Moment Correlation Test, (6) and Significance Test (test t)The results of the research that the author did using the product moment formula obtained by the rxy result, the correlation coefficient number with rtable results df = n-2 (17-2) = 15 at a significant level of 5% of 0.514, it turns out that the correlation coefficient number or rcount (0.789 ) and is greater than the rtable value (0.789 > 0.514), meaning that the variable (X) has an effect on the variable (Y). Furthermore, the results of t-count show that the value of tcount > ttable (4.97 > 2.132), which means that H0 is rejected and Ha is accepted. In conclusion, the Recitation method has an influence on student learning outcomes in Islamic Cultural History (SKI) class VIII at MTs .Muhammadiyah 8 Sidokelar